ANALISIS TINGKAT KEMAMPUAN LITERASI STATISTIK SISWA SMA SEDERAJAT BERDASARKAN MUTU SEKOLAH - Hadi Kusmanto (IAIN Syekh Nurjati Cirebon, 2017)
ABSTRACTStatistical literacy is a skill that must be owned by the students through the learning process in all levels of education. Students who have good statistical literacy skills will be easier to solve the problems of everyday life, scientific activities, activities of science and learning. Learning statistics at this point is still influenced by the traditional way of learning, and more emphasis on derivation is still a lot, making it difficult for students to understand. This study aims to determine the statistical literacy skills equivalent to high school students in the city of Cirebon, knowing the difference statistical literacy skills equivalent to high school students based on the quality of schools, and identify opportunities statistical literacy skills of students based on the quality of schools. This research was conducted at the high school level or equivalent using a quantitative study presented by the research design ANOVA row single column. The population in this study were all high school or equivalent in Cirebon. The sample was taken using the Proportionate Stratified Random Sampling. This research data retrieval technique using the test to take three schools for school quality is low, medium, and high. The results showed statistical literacy skills equivalent of high school students in the city of Cirebon included in the classification being. There are differences in the average statistical literacy skills of students by school quality (high, medium, and low), with the quality of high schools tend to have a statistically better literacy skills than school quality medium, and low. The results of analysis of opportunities using conditional probability theory state that the statistical literacy skills of students based on the quality of schools that are in the medium classification. Keyword: analysis, ability students, literacy statistics, quality of schools